ANALYSIS OF METABOLITES PRESENT IN ULTRASONICALLY TREATED KARUPU KAVUNI BY USING GC-MS/FID - TNA, ARUNASREE; BHUVANA, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The Investigation of metabolites present in the ultrasonically treated kavuni rice are determined by the GC-MS/FID. In this study the karupu kavuni rice is ultrasonically treated at the temperature of 30⁰C &45⁰C and examined for the metabolites by using the GC-MS/FID more than twenty active compounds are identified and found at the different peak heights. At ultrasound treatment 30⁰C and 45⁰C, the highest peak was found at the 18.1min and metabolite found as cis-13-Octadecenoic acid. In untreated kavuni rice similar types of the compounds was identified. Hence this study proves that the ultrasound treatment on the rice, retains the metabolites, present in the kavuni rice.